Experience of Endoscopic Ultrasound Guided Fine Needle Aspiration and Fine Needle Biopsy: Data from Tertiary Care Hospital in Pakistan: Endoscopic Ultrasound Guided Fine Needle Aspiration and Biopsy - Mushtaq, Hafiz Irfan; Shams, Fariha; Rasool, Shafqat; Hassan, Ghias Ul; Jabbar, Sadia; Javed, Farwa; Rasheed, Sidra; Dlishad, Akif; Tayyab, Ghias Un Nabi (Pakistan Journal of Health Sciences, 2024)
Endoscopic ultrasound guided fine needle aspiration and biopsy (EUS-FNA/FNB) are minimally invasive and yet very effective techniques for tissue acquisition and diagnosis of sub-epithelial or other lesions in close premises of gastrointestinal tract. Objective: To evaluate the diagnostic accuracy and safety of the EUS-FNA FNA/FNB in various lesions. Methods: This was a single center study of consecutive 189 patients who presented to Gastroenterology department of Lahore General Hospital, Lahore for EUS FNA/FNB during October 2019 to March 2023. Results: 189 patients undergoing EUS-FNA/FNB, 60% were males, 40% females. Mean age was 48.84±15.96 years. EUS-FNA and FNB was done in 28 (14.8%) and 161 (85.2%) patients respectively. Median number of passes was 3 (IQR: 1-4). Most of the lesions were of pancreatic origin (n=110, 58.2%) pancreatic adenocarcinoma was found in 69.3 % solid pancreatic lesions. Other lesions were abdominal/mediastinal lymphadenopathy (n=37, 19.5%), gastric (n=26, 13.8%) and liver (n=10, 5.3%). Malignant lesions were found in 105 (55.6%) cases, benign diseases (n=34, 18%) and normal tissue (n=12, 6.3%).The overall diagnostic yield was 151/179(79.9%) with comparable yield of EUS-FNA and FNB, 21/28(75%) and 130/161 (80.7%) respectively (p=0.06).Complications rate was 2.1%. Conclusions: EUS FNA/FNB is effective and safe technique for evaluation of suspicious lesions in or around the gastrointestinal tract especially pancreatic lesions and further studies are needed to establish the best technique to improve tissue acquisition.